Opioid-sparing versus opioid-free anesthesia following cancer surgery : Effect on pain severity and patient-reported outcomes - Dananjaya, Vigyan; Adi Santika, Suparno (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Opioid use in anesthesia during cancer surgery causes concerns about adverse effects, including postoperative nausea, vomiting, respiratory depression, and potential impacts regarding cancer recurrence. In response, opioid-sparing and opioid-free anesthesia procedures have emerged as promising strategies to reduce opioid consumption while maintaining effective pain management. This study aimed to analyze the outcome of opioid-sparing anesthesia compared to opioid-free anesthesia on pain severity and patient-reported outcomes following cancer surgery. Randomized controlled trials and observational research that met predefined inclusion criteria were systematically selected, with data extracted and analyzed. The analysis revealed that both opioid-sparing and opioid-free anesthesia techniques reduced postoperative pain severity significantly in comparison to traditional opioid-based anesthesia. Additionally, patients who received opioid-free anesthesia reported better overall outcomes, including reduced nausea, faster recovery times, and improved satisfaction scores. Although pain control differences between opioid-sparing and opioid-free anesthesia techniques were statistically insignificant, both techniques showed substantial as safer, effective alternatives in perioperative cancer care, supporting their broader adoption in clinical practice.